Optimasi Perencanaan Produksi Sepatu Kulit Dengan Menggunakan Linier Programming - Yusnita, Erni; Juarni, Juarni (Universitas Medan Area, 2018)
CV. Kotama Shoes is a trading company engaged in the production of leather shoes. The company is located on Jalan A.R. Judge No.112c / 206c. In running its business, CV. Kotama Shoes has several problems or constraints in production planning. Erratic fluctuations in demand for goods from one period to another cause a deficiency or excess production. Based on the results of data processing, the smallest MSE forecasting results for each product, namely for pantofel products, has the smallest MSE value 21495.23, the chosen method is the moving average with a 6-month moving average value, the smallest MSE product 18779.38 method the chosen ones are weighted moving average with a moving average value of 3 months, boot products with the smallest MSE 1175.47 the selected method is a moving average with a moving average of 6 months and semi boot products with the smallest MSE 4119.34 the method chosen namely the weighted moving average with a moving average of 3 months. The calculation results using linear programming with the POM for Windows software tool shows that the production costs applied by CV. Kotama Shoes is a minimum. The minimum level obtained is Rp. 37,502,700, - Production planning for pantofel products is 420 units, production planning for casual leather shoes is 309 units, demand for semi boot boot leather units is 194 units, demand for leather shoes production is 177 units boot type.